Enhancing the Solubility of Co-Formulated Hydrophobic Drugs by Incorporating Functionalized Nano-Structured Poly Lactic-co-glycolic Acid (nfPLGA) During Co-Precipitation - Mohammad Saiful Islam; Somenath Mitra (Pharmaceutics)
Background/Objectives: The co-formulation of active pharmaceutical ingredients (APIs) is a growing strategy in biopharmaceutical development, particularly when it comes to improving solubility and bioavailability. This study explores a co-precipitation method to prepare co-formulated crystals of griseofulvin (GF) and dexamethasone (DXM), utilizing nanostructured, functionalized polylactic glycolic acid (nfPLGA) as a solubility enhancer. Methods: An antisolvent precipitation technique was employed to incorporate nfPLGA at a 3% concentration into the co-formulated GF and DXM, referred to as DXM-GF-nfPLGA. The dissolution performance of this formulation was compared to that of the pure drugs and the co-precipitated DXM-GF without nfPLGA. Results: Several characterization techniques, including electron microscopy (SEM), RAMAN, FTIR, TGA, and XRD, were used to analyze the nfPLGA incorporation and the co-precipitated co-formulations. The inclusion of nfPLGA significantly enhanced the dissolution and initial dissolution rate of both GF and DXM in the DXM-GF-nfPLGA formulation, achieving a maximum dissolution of 100%, which was not attained by the pure drugs or the DXM-GF formulation. The incorporation of nfPLGA also reduced the amount of time taken to reach 50% (T50) and 80% (T80) dissolution. T50 values decreased from 52 and 82 min (for pure DXM and GF) to 23 min for DXM-GF-nfPLGA, and the T80 improved to 50 min for DXM-GF-nfPLGA, significantly outpacing the pure compounds. Furthermore, incorporating nfPLGA into the crystal structures greatly accelerated the dissolution rates, with initial rates reaching 650.92 µg/min for DXM-GF-nfPLGA compared to 540.60 µg/min for DXM-GF, while pure GF and DXM showed lower rates. Conclusions: This work demonstrates that nfPLGA incorporation enhances dissolution performance by forming water channels within the API crystal via hydrogen-bonding interactions. This innovative nfPLGA incorporation method holds promise for developing hydrophobic co-formulations with faster solubility and dissolution rates.